Chapter Le traduzioni russe della Vita di Cimabue di Giorgio Vasari: strategie traduttive a confronto - Papini, Gabriele (Lessico multilingue dei Beni Culturali, 2023)
This chapter takes into consideration two Russian translations of the Vita of Cimabue. One of these presents a selection from Le Vite de' più eccellenti pittori, scultori, e architettori by Giorgio Vasari and is dated 1933; the other is the first complete Russian translation of Vasari's Vite published between 1956 and 1971. The comparison of these two translations focuses on morphological, lexical and syntactical aspects of the original version. Particular attention is devoted to the translation of inter-phrasal and intra-phrasal connectors, of the coniunctio relativa and of gerunds. The chapter also reflects on the translation of Latin inscriptions, toponyms and proper nouns.